Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Yang, Shiyi; Bai, Yanhan; Tao, Junjie; Tu, Chengming; Chen, Bing; Huang, Xiaoman; Zhang, Linpeng; Liu, Lihan; Li, Lin; Qin, Zhendong (Fish & shellfish immunology, 2024)
In teleost blood, red blood cells (RBCs) are the most common type of cell, and they differ from mammalian RBCs in having a nucleus and other organelles. As nucleated cells, teleost RBCs contribute to the immune response against pathogens, but their antibacterial mechanism remains unclear. Here, we utilized RNA-Seq to analyze gene expression patterns of grass carp (Ctenopharyngodon idellus) RBCs (GcRBCs) stimulated by Aeromonas hydrophila, Escherichia coli, and Staphylococcus aureus. Our transcriptomic data showed that bacterial stimulation generated many differentially expressed genes (DEGs). Furthermore, several inflammatory pathways responded to bacterial activation, and the TLR, IL-17, and tumor necrosis factor (TNF) signaling pathways were significantly activated based on Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. Furthermore, the findings of qRT-PCR showed markedly elevated expression of various cytokines, including IL-1β, IL4, IL6, IL8, IL12, and TNFα, in GcRBCs after incubation with bacteria. Reactive oxygen species (ROS) production in GcRBCs was markedly increased after the cells were stimulated with the three bacteria, and the expression of superoxide dismutase, glutathione peroxidase, and antioxidant enzymes, including catalase, was altered. Flow cytometry analysis showed that the apoptosis rate of GcRBCs was enhanced after stimulation with the three bacteria for different times. In summary, our findings reveal that bacterial stimulation activates the immune response of GcRBCs by regulating ROS release, cytokine expression, and the antioxidant system, leading to apoptosis of GcRBCs. •The stimulation of bacteria activated the immune response of erythrocytes.•The stimulation of bacteria activated the antioxidant enzymes system of erythrocytes.•The incubation of bacteria caused apoptosis of erythrocytes.